Modeling to better inform food, energy, and water policies: Country perspective - Rosegrant, Mark W. (2016)
Mark Rosegrant Global Landscapes Forum IFPRI Session: Informing the policymaking landscape: From research to action in the fight against climate change and hunger Marrakech, Morocco November 16, 2016